Cover Image, Volume 38, Number 6, August 2019. Issue 6 (26th July 2019) - van Kerrebroeck, Philip E. V. A.; Reekmans, Mathias; van Koeveringe, Gommert A.; Yeh, Alexander J.; Fayram, Timothy A.; Sharan, Ashwini D.; Comiter, Craig V.
Abstract : The Front Cover : The cover image is based on the ORIGINAL CLINICAL ARTICLE First‐in‐human implantation of a mid‐field powered neurostimulator at the sacral nerve: Results from an acute study by Philip E. V. A. van Kerrebroeck et al., https://doi.org/10.1002/nau.24035 . Cover Credit: Cover image © Amerra Animation Images